2005
DOI: 10.1128/aem.71.8.4318-4324.2005
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Enterobacterial Repetitive Intergenic Consensus PCR Types of Campylobacter coli and Campylobacter jejuni by Fourier Transform Infrared Spectroscopy

Abstract: Fourier transform infrared spectroscopy (FT-IR) has been used together with pattern recognition methodology to study isolates belonging to the species Campylobacter coli and Campylobacter jejuni and to compare FT-IR typing schemes with established genomic profiles based on enterobacterial repetitive intergenic consensus PCR (ERIC-PCR). Seventeen isolates were cultivated under standardized conditions for 2, 3, and 4 days to study variability and improve reproducibility. ERIC-PCR profiles and FT-IR spectra were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 55 publications
1
60
0
3
Order By: Relevance
“…There are several factors (parameters) that may affect vibrational spectrum reproducibility, including cell culture age, nutrient availability, cultivation temperature, and spectral wavenumber selection (42). In addition, vibrational spectral variability was due mainly to biological features and to a lesser extent to instrumental sources (55). This statement was further validated in this study by using two different Raman instruments.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…There are several factors (parameters) that may affect vibrational spectrum reproducibility, including cell culture age, nutrient availability, cultivation temperature, and spectral wavenumber selection (42). In addition, vibrational spectral variability was due mainly to biological features and to a lesser extent to instrumental sources (55). This statement was further validated in this study by using two different Raman instruments.…”
Section: Methodsmentioning
confidence: 92%
“…In the case of Raman spectroscopy, there are several factors that may affect spectral reproducibility, including bacterial cultivation time, growth temperature, medium use, and wavenumber selection (42,43,55). We calculated the D y1y2 values and demonstrated that use of the wavenumber region of 1,800 to 650 cm Ϫ1 provided the lowest D y1y2 value, indicating that the highest reproducibility of Raman spectra would be within this wavelength range (55). Fortunately, this spectral range includes important features for proteins, polysaccharides, nucleic acids, and lipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One strain (C-600) remained unclustered. FT-IR spectroscopy has high discriminatory power at the subspecies level (Mouwen et al, 2005;Mouwen et al, 2011), including for E. coli (Davis et al, 2012;Sousa et al, 2013;Dawson et al, 2014;Prieto-Calvo et al, 2014). The current study also showed a significant level of agreement between certain groupings (strains MF2494, MF2522 and MF3578; strains EDL933 and MF3582) when using FT-IR spectra and ribotyping or ITS rRNA gene sequencing (Figure 2).…”
Section: Carbon Source Utilisation Resultsmentioning
confidence: 51%
“…Recently, ERIC-PCR was used for the evaluation of genetic analysis and epidemiology investigation of some pathogens such as Vibrio parahaemolyticus, Campylobacter, Escherichia coli, Salmonella enterica and Aeromonas sp. strains (Versalovic et al, 1991;Wong and Lin, 2001;Da Silverra et al, 2002;Mclellan et al, 2003;Szczuka and Kaznowski, 2004;Houf et al, 2005;Mouwen et al, 2005). However, little attempt has been focused on the typing of Ent.…”
Section: Introductionmentioning
confidence: 99%